Pengembangan LKPD Berbasis Liveworksheets pada Pembelajaran IPAS Kelas IV Sekolah Dasar Negeri 39 Pontianak Kota - Rahayu, Beti; Kartono, Kartono; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The research aims to produce student worksheets based on Liveworksheets application in fourth-grade natural and social science classes at SDN 39 Pontianak Kota, fulfilling the criteria of didactics, construction, and technical aspects, in addition to describing students' responses to the developed product. The research and development method utilized was the ADDIE development model (analysis, design, development, implementation, and evaluation). The research and development process involved assessments from professionals using a product validation questionnaire, the average scores obtained for the didactic aspect were 3.88 (highly suitable criteria), for the construction aspect were 3.53 (highly suitable criteria), and for the technical aspect were 3.80 (highly suitable criteria). The practicality response of the product through a questionnaire by students obtained an average percentage of 90.95% on a small scale and 93.82% on a large scale, indicating that students generally agreed that the product was highly practical.